A SOCIOLINGUISTIC ANALYSIS OF VARIOUS SPORTS JARGON INSIDE THE UNITED INDONESIA MAGAZINE - Hikmah Pravitasari (English Didactic, 2021)
In general there are four types of language varieties in sociolinguistic study; they are slang, register, jargon, and argot. Jargon is one of language varieties in sociolinguistics. Jargon is the feature of language variety which is used for specific field and just understood by them who stand on those specific fields, but it is not secret. The forms of jargon are abbreviation, acronymn, word, and phrase. This research aimed to know the jargon used in United Indonesia Magazine. In this study, the researcher applied the descriptive qualitative method. The source of the data is several articles publised in the United Indonesia Magazine. The researcher employed a document analysis technique to collect the research data. This technique is carried out by observing and determining the articles which contains Jargon. The result of this research found 8 sport jargons used in the United Indonesia Magazine. From the 8 data, four jargon was in the form of words and four jargon in the form of phrases. This research found some functions of jargon that were giving a person a sense of belonging to a specific group, making it easier for a person to communicate with their group, and as an effective signal for identification.